IMPLEMENTASI KEPMEN NOMOR 48 TAHUN 2004 TENTANG TATA CARA PEMBUATAN DAN PENGESAHAN PERATURAN PERUSAHAAN DAN PERJANJIAN KERJA BERSAMA DIKABUPATEN PELALAWAN TAHUN 2012 - Arief, Roesyandi Nan; Ridwan, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Ministerial Decree number 48 of 2004 is a ministerial decree regulating the manufacture and validation procedures as well as the making of Company Regulations and Collective Labor Agreements registration. The method used is descriptive analysis with the aim to provide a picture or painting the situation in a systematic, factual and accurate information on the implementation of a policy on procedures for the making and ratification of the Company's Regulations as well as the creation and registration of the PKB. Qualitatively analyzed both quantitative data and qualitative nature based on reports and records that exist in the field. The data collected with the study of literature (library research) and field studies (field research) which observations and interviews. The results showed that PT. Arara Abadi and PT. LIH has complied and run the ministerial decree number 48 of 2004 PT. Arara Abadi has company regulations and collective agreements in accordance with government regulations. In addition, PT. LIH also have to have the company rules and collective bargaining agreements.Keyword : Decree No. 48 Year 2004 on the Procedures for Making and Legalization of Company Regulations and Collective Labor Agreement